2022
DOI: 10.1002/mde.3679
|View full text |Cite
|
Sign up to set email alerts
|

Mixed ownership reforms and the transparency of nonstate‐owned enterprises: Evidence from China

Abstract: This paper takes Chinese Shanghai and Shenzhen A‐share nonstate‐owned listed companies from 2008 to 2019 as samples to study the impact and mechanism of state‐owned capital participation on the transparency of nonstate‐owned enterprises. The results show that state‐owned capital participation has a significant positive impact on the transparency of nonstate‐owned enterprises. In terms of the mechanism of action, state‐owned capital participation positively impacts corporate transparency by increasing investors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The choice of control variables is based on three main considerations: First, at the level of firm characteristics, environmental investment is an investment behavior of firms and is necessarily influenced by firm fundamentals, so with reference to previous literature (Porter and Linde, 1995;Tang et al, 2013;Hu et al, 2017;Feng and Sun, 2020), we control for variables such as firm age (Age), firm size (Size), firm growth (Growth), profitability (ROA), financial leverage (Lev), capital expenditure (Capx) and operating cash flow (Cfo). Second, at the level of internal corporate governance, factors such as shareholding structure, board structure, and executive characteristics can indirectly affect the environmental governance level by influencing firms' investment decisions (Carl et al, 2012;Tao and Liu, 2013;Schaltenbrand et al, 2018;Dyck et al, 2019;Zhao and Mao, 2022), so we also control for the proportion of institutional shareholding (INSR), board size (Board), the proportion of independent directors (Indp), and dual employment (Dual) variables. Third, at the level of the firm's external environment, according to previous literature (Orsato, 2006;Gao and Zheng, 2017;Zhou and Shen, 2019), the degree of market competition of the enterprise and the strength of government environmental regulation also have an impact on the environmental governance of a firm at a certain period, so we also control for the variables of industry concentration (HHI) and the environmental regulation effects (ER).…”
Section: Variable Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of control variables is based on three main considerations: First, at the level of firm characteristics, environmental investment is an investment behavior of firms and is necessarily influenced by firm fundamentals, so with reference to previous literature (Porter and Linde, 1995;Tang et al, 2013;Hu et al, 2017;Feng and Sun, 2020), we control for variables such as firm age (Age), firm size (Size), firm growth (Growth), profitability (ROA), financial leverage (Lev), capital expenditure (Capx) and operating cash flow (Cfo). Second, at the level of internal corporate governance, factors such as shareholding structure, board structure, and executive characteristics can indirectly affect the environmental governance level by influencing firms' investment decisions (Carl et al, 2012;Tao and Liu, 2013;Schaltenbrand et al, 2018;Dyck et al, 2019;Zhao and Mao, 2022), so we also control for the proportion of institutional shareholding (INSR), board size (Board), the proportion of independent directors (Indp), and dual employment (Dual) variables. Third, at the level of the firm's external environment, according to previous literature (Orsato, 2006;Gao and Zheng, 2017;Zhou and Shen, 2019), the degree of market competition of the enterprise and the strength of government environmental regulation also have an impact on the environmental governance of a firm at a certain period, so we also control for the variables of industry concentration (HHI) and the environmental regulation effects (ER).…”
Section: Variable Selectionmentioning
confidence: 99%
“…First, we expand the research in the area of economic consequences for state-owned participation shareholders from the perspective of corporate environmental governance. Studies on stateowned participation shareholders have mainly focused on enterprise investment and financing (Li et al, 2021), cash flow level (Wei and Song, 2020), TFP (Yin et al, 2018), enterprise transparency (Zhao and Mao, 2022), enterprise innovation (Luo and Qin, 2019) and performance (Yu et al, 2017)aspects. For example, Li et al (2021) found that state-owned shares within private firms, which act as political affiliations, help them to obtain more bank loans and longer loan terms.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed ownership reform has always encouraged both private enterprises and state‐owned enterprises to embed themselves through cross‐shareholding, aims to amplify the functions of state‐owned capital, and realizes the preservation and appreciation of state‐owned assets, thus promoting the healthy development (Zhao & Mao, 2022). In the reform, the incorporation of state‐owned equity by private enterprises not only helps to broaden the channels to seek capital (Song et al, 2017) but also contributes to improving the corporate governance ability and achieving the combination of institution and market advantages.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…However, at present, state-owned capital is undergoing a transformation process from state-owned assets management to equity management (Zhao & Mao, 2022). Partially, shareholding in other enterprises has become an important form of assets realization (Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Here are some potential contributions of this study: first, our findings enrich the research on the economic consequence of reverse mixed ownership reform. The existing literature has explored the economic consequence of Chinese reverse mixed ownership reform from the perspective of risk-taking, transparency, and corporate social responsibility [6,12,13], but studies regarding green innovation are relatively rare. Facing serious environmental problems, we take the participation of state-owned capital as an opportunity to confirm the positive enhancement effect of reverse mixed ownership reform on POEs' green innovation in China.…”
Section: Introductionmentioning
confidence: 99%